2015
DOI: 10.1002/anie.201503393
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nitrate Mediated Regioselective [2+2+1] Cyclization of Alkynes with Alkenes: A Cascade Approach to Δ2‐Isoxazolines

Abstract: An efficient method for the regioselective synthesis of pharmacologically relevant polysubstituted Δ(2)-isoxazolines is based on the copper-mediated direct transformation of simple terminal alkynes and alkenes. The overall process involves the formation of four chemical bonds with inexpensive and readily available copper nitrate trihydrate as a novel precursor of nitrile oxides. The reaction can be easily handled and proceeds under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 58 publications
1
29
0
1
Order By: Relevance
“…The key steps of the cycle are consistent with the precedentss et by Itoh [36,37] or Xu. [43] Uniquely in this work, the presence of an itryl radical from N-nitrosuccinimide under photoredox conditions sets in motion the a-nitration of acetonel eading to an in situ oxidation providing the 3-acetyl nitrile oxide. [44] The corresponding dipole leads unexceptionally to a1 ,3-dipolar cycloaddition with as uitable dipolarophile furnishingt he desired heterocycle.T ot est this hypothesis, the reactionw as performed in the absence of ap hotocatalyst while maintaining irradiation under otherwise standard conditions.…”
Section: Mechanistic Investigations For the Synthesis Of Isoxazoline mentioning
confidence: 99%
“…The key steps of the cycle are consistent with the precedentss et by Itoh [36,37] or Xu. [43] Uniquely in this work, the presence of an itryl radical from N-nitrosuccinimide under photoredox conditions sets in motion the a-nitration of acetonel eading to an in situ oxidation providing the 3-acetyl nitrile oxide. [44] The corresponding dipole leads unexceptionally to a1 ,3-dipolar cycloaddition with as uitable dipolarophile furnishingt he desired heterocycle.T ot est this hypothesis, the reactionw as performed in the absence of ap hotocatalyst while maintaining irradiation under otherwise standard conditions.…”
Section: Mechanistic Investigations For the Synthesis Of Isoxazoline mentioning
confidence: 99%
“…Copper nitrate trihydrate has been used as a nitration reagent 13 and catalyst. 14 Recently, an elegant protocol of copper nitrate mediated annulation of alkynes and alkenes was firstly developed to afford Δ 2 -isoxazolines. 15 In order to achieve the pharmacologically interesting isoxazoles more efficiently, 16 we envisioned to synthesize isoxazoles from two different alkynes in the presence of copper nitrate. However, two main hurdles for this transformation need to be resolved to realize this facile construction (Scheme 1): 1) it's a challenge to avoid the undesired formation of Glaser-Hay homocoupling 1,3-diyne by-products from each of the alkynes; 17 2) how to improve the chemo-and regioselectivity in the initiation and annulation steps with all the substrates assembled in the desired position of final products.…”
Section: Scheme 1 Design and Challenges For Synthesis Of Isoxazolesmentioning
confidence: 99%
“…No reaction or less effective results could be observed using other nitrogen sources such as 6 , KNO 3 or tBuONO, which implied that copper nitrate was essential to the success of this transformation (entries 8-12). The yield was decreased when lowering the loading of the copper salt or changing the reaction temperature (entries [13][14][15]. Further investigations suggested that an inert atmosphere could benefit the reaction, while low yield was observed under aerobic or oxygen atmosphere (entries 16 and 17).…”
Section: Scheme 1 Design and Challenges For Synthesis Of Isoxazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an efficient synthesis of polysubstituted Δ 2 ‐isoxazolines 33 was disclosed from simple terminal alkynes 31 and alkenes 32 through a novel copper nitrate trihydrate‐mediated regioselective [2 + 2 + 1] cyclization, where copper nitrate acted as the catalyst and a novel nitrogen source as well (Scheme ) 37. This convenient and practical approach features good yields, wide substrate scope, good functional group tolerance, and high modularity.…”
Section: Copper Nitratementioning
confidence: 99%